Konsep Fisika Perpindahan Panas dalam Kearifan Lokal Miyang Tuban - Muthi'ah, Lathifatul; Admoko, Setyo; Krisanti, Galuh Dwi; Mahfudloh, Durriyah Amirotul; Damarsha, Adrian Bagas (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Physics learning faces serious challenges as students perceive physics as a complex subject that is difficult to implement in daily life. This research aims to explore the local wisdom of fishermen in